(untitled) (International Conference on Computers in Education, 2020)
The social distancing measures that have been adopted in response to the COVID-19 pandemic have resulted in the implementation of emergency remote teaching (ERT) practices in many educational contexts. This shift has presented several challenges, including issues of technological accessibility. A survey was conducted of members of Online Teaching Japan, a grass-roots professional learning community which was created to support teachers’ transitions to ERT. This paper will report on the results of this survey that address accessibility issues.